THE EFFECT OF MULTI-STEP FLOW OF COMMUNICATION ON SOCIAL AGENCY FARMING FACTORS IN JAROREJO VILLAGE - Hyan Oktodia Basuki; Hanim Nur Faizah; Dyah Pitaloka (Jurnal Penelitian, 2021)
Early marriage is defined as a marriage that occurs before a child has 18 years of age. Indonesia was ranked 37th and the second highest ASEAN after Cambodia. Factors that cause marriage at an early age include social and cultural influences, the environment of residence, family, and the role of parents. This research is a pre-experimental study with a one-group pre-post design approach. The study sample was 28 housewives with a simple random sampling technique. The independent variable of the research is the multi-step flow of communication. The dependent variable is the social factor of maturing the age of marriage. Data analysis using the Wilcoxon test with a significant level of p-value ≤ 0.05. Calculated obtained p-value = 0,000 (≤ 0.05) means that H1 is accepted or there is a multi-step flow of communication influence on social factors maturing the age of marriage. The conclusions that can be taken by the multi-step flow of communication can influence social factors in maturing the age of marriage in 3 stages. In the third stage, complex communication is created and there is a process of discussion between groups so that it can increase the knowledge and duties of the role of parents in maturing the age of marriage.